Hand-held devices for generating force/torque perturbations - Wong, Yoke Cung. (2011)
There have been many studies dealing with sudden muscle stretch experienced by people who suffer from Parkinson’s diseases. As one of the methods to observe this passive muscle activity on the upper limb, researchers utilize devices that capable of creating passive angular motions of the wrist. Encouraged by this need, a simple hand-grasped device for wrist perturbation is proposed in this work and its ability to generate torque is investigated. The system is driven by a DC motor and mainly consists of a flywheel, a handle, and a breaking system. The working principle is to spin the flywheel at a certain angular speed and then break this rotation motion within a very short period so that relatively high deceleration will take place and torque will be generated. The conducted experiments show that the torque exerted by the combination of the flywheel's inertia, angular speed, and breaking-off time interval enables the device to generate passive angular displacement of the wrist.